Light to moderate long-term grazing enhances ecosystem carbon across a broad climatic gradient in northern temperate grasslands - Bork, Edward W.; Hewins, Daniel B.; Lamb, Eric G.; Carlyle, Cameron N.; Lyseng, Mark P.; Chang, Scott X.; Alexander, Michael J.; Willms, Walter D.; Iravani, Majid (The Science of the total environment, 2023)
Grasslands are globally abundant and provide many ecosystem services, including carbon (C) storage. While grasslands are widely subject to livestock grazing, the influence of grazing on grassland ecosystem C remains unclear. We studied the effect of long-term livestock grazing on C densities of different ecosystem components in 110 northern temperate grasslands across a broad agroclimatic gradient in Alberta, Canada. These grasslands stored 50 to 180 t ha−1C in live and dead vegetation, as well as soil C to 30 cm depth, with the majority as soil organic C (SOC). The mulch layer comprised a large amount of C (~18 t ha−1C) especially within humid grasslands. Although grazing reduced C densities in litter mass, total ecosystem C was 8.5 % greater under grazing (127.8 t ha−1) compared to those non-grazed (117.8 t ha−1), primarily due to increases in SOC and roots. Increases in SOC were consistently observed in the 0–15 cm layer across all climatic conditions, with changes in SOC of the 15–30 cm layer inversely related to aridity. A structural equation model revealed that increased SOC under grazing was indirectly attributed to increases in eudicot rather than graminoid biomass. In addition, SOC increased with graminoid quality (i.e., a reduced carbon to nitrogen ratio), which together with elevated eudicots, increased litter and mulch C, and ultimately enhanced SOC densities. When applied to spatial maps of habitat type and land use (livestock grazing) activity across the region, an area of ~3.8 M ha of grassland was projected to contain an additional 17.1 M t of C under grazing, primarily in mesic grasslands, worth an estimated $3.1 B (Cdn.) under current C valuation guidelines in Canada. Overall, these results highlight the importance of grasslands for C storage and establishing policies that maintain and promote their sustainable use, including light to moderate grazing. [Display omitted] •Grasslands subject to long-term grazing increased ecosystem carbon stock from 117.8 to 127.8 t ha−1.•Increases in soil C under grazing offset reductions in C within plant litter•Greater soil C under grazing was associated with increased eudicot biomass and lower graminoid C:N ratio.•Modelled increases in grassland ecosystem C under grazing were 17.1 M tonnes, worth >$3.1 B Cdn.